Risk Comparison Using Autologous Dermal Flap and Absorbable Breast Mesh on Patient Undergoing Subcutaneous Mastectomy with Immediate Breast Reconstruction - Patzelt, Matej; Zárubová, Lucie; Vecerova, Michaela; Barta, Josef; Ouzky, Martin; Sukop, Andrej (Aesthetic plastic surgery, 2022)
In patients with large breasts undergoing a subcutaneous mastectomy with immediate implant-based reconstruction, is necessary to perform a mastopexy. The combination of these procedures increases the complication rate. To reduce it, it is necessary to cover the lower pole of the implant. Our study aimed to compare the use of an autologous dermal flap and an absorbable breast mesh. A total of 64 patients without previous breast surgery were divided into 2 groups, each with 32 patients. In the 1st group, the implant was covered with an autologous caudally based dermal flap, sutured to the great pectoral muscle. In the 2nd group, the implant was covered with a fully absorbable breast mesh, fixed caudally in the inframammary fold and cranially to the great pectoral muscle. The incidence of complications, the aesthetic effect, and patient satisfaction were evaluated in a one-year follow-up. In the 1st group, there were 2 cases of seroma, 2 partial nipple-areola complex necrosis, 4 cases of dehiscence in the T-suture, and the malposition of the implant in 2 patients. In the 2nd group, there were 2 cases of seroma, 2 cases of T-junction dehiscence, and 1 case of full nipple-areola complex necrosis, which resulted in implant loss. There was no significant difference in patient satisfaction between the study groups. The dermal flap is more suitable for breasts with pronounced ptosis. The use of the synthetic mesh is suitable for smaller breasts, where the possible dermal flap would be too small to cover the implant. LEVEL OF EVIDENCE IV: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .
Keywords: subkutánní mastektomie; chirurgické síťky; nádory prsu; Mammaplasty; prsní bradavky; Female; výsledek terapie; Mastectomy; ženské pohlaví; lidé; nekróza; Breast Neoplasms; Treatment Outcome; Necrosis; Nipples; retrospektivní studie; mastektomie; serom; Retrospective Studies; mamoplastika; Seroma; Surgical Mesh; Mastectomy, Subcutaneous; Humans